(untitled) (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2013)
Water shortage is one of the main issues in Jericho area in Palestine, hampering further development of agriculture. A higher amount of water suitable for irrigation would render a significant growth of the agricultural market and the associated branches possible and thus be of great economical advantage. Not only is the current water shortage problematic for farmers, but it is to be expected that it will increase in near future. More water is needed, but less is available due to less rainfall. Still, additional brackish water would be available, but its usage would endanger soil quality in the long run. Desalination is a possible solution. The study presented in this contribution is consists therefore of a field survey of 25 questionnaires was carried out for the analyses for the community acceptance towards using desalination units for saline and brackish water for agricultural irrigation. The average cost of one cubic meter of the desalinized water that is accepted by the participants of the survey for agricultural use is 0.25 Euro, which is equal or less than the current pumping costs for non-desalinated water. The majority of surveyed well owners estimate that their crop productivity will be increased by 40 to 60 percent after using the units. This will increase also the annual water consumption to its one third to one half more than its usual water consumption rate (700 1200 cubic meter for each dunum per year, 1 dunum = 1000 m2). Variability in crop sorts will be added in addition to raw and cooked grown vegetables as well as of grown Palm trees. A majority of the farmers (95%) thinks that the long-term use of saline water will destroy the fertility of the soil as well as the crop agricultural cycle in the area.